Pharmacogenomics in kidney transplant recipients and potential for integration into practice. (14th July 2020) - Nguyen, Tam T.; Pearson, Rachael A.; Mohamed, Moataz E.; Schladt, David P.; Berglund, Danielle; Rivers, Zachary; Skaar, Debra J.; Wu, Baolin; Guan, Weihua; van Setten, Jessica; Keating, Brendan J.; Dorr, Casey; et al.
Abstract: What is known and objective: Pharmacogenomic biomarkers are now used in many clinical care settings and represent one of the successes of precision medicine. Genetic variants are associated with pharmacokinetic and pharmacodynamic changes leading to medication adverse effects and changes in clinical response. Actionable pharmacogenomic variants are common in transplant recipients and have implications for medications used in transplant, but yet are not broadly incorporated into practice. Methods: From the Clinical Pharmacogenetics Implementation Consortium and Dutch Pharmacogenetics Working Group guidelines, and PharmGKB databases, 12 pharmacogenomic genes with 30 variants were selected and used to create diplotypes and actionable pharmacogenomic phenotypes. A total of 853 kidney allograft recipients who had genomic information available from a genome‐wide association study were included. Results: Each recipient had at least one actionable pharmacogenomic diplotype/phenotype, whereas the majority (58%) had three or four actionable diplotypes/phenotypes and 17.4% had five or more among the 12 genes. The participants carried actionable diplotypes/phenotypes for multiple medications, including tacrolimus, azathioprine, clopidogrel, warfarin, simvastatin, voriconazole, antidepressants and proton‐pump inhibitors. What is new and conclusion: Pharmacogenomic variants are common in transplant recipients, and transplant recipients receive medications that have actionable variants. Clinical trial: Genomics of Transplantation, clinicaltrials.gov (NCT01714440).